Divergent effects of oxytocin on (para-)limbic reactivity to emotional and neutral scenes in females with and without borderline personality disorder - Lischke, Alexander; Herpertz, Sabine (Social cognitive and affective neuroscience, 2017)
Borderline personality disorder (BPD) patients’ hypersensitivity for emotionally relevant stimuli has been suggested be due to abnormal activity and connectivity in (para-)limbic and prefrontal brain regions during stimulus processing. The neuropeptide oxytocin has been shown to modulate activity and functional connectivity in these brain regions, thereby optimizing the processing of emotional and neutral stimuli. To investigate whether oxytocin would be capable of attenuating BPD patients’ hypersensitivity for such stimuli, we recorded brain activity and gaze behavior during the processing of complex scenes in 51 females with and 48 without BPD after intranasal application of either oxytocin or placebo. We found divergent effects of oxytocin on BPD and healthy control (HC) participants’ (para-)limbic reactivity to emotional and neutral scenes: Oxytocin decreased amygdala and insula reactivity in BPD participants but increased it in HC participants, indicating an oxytocin-induced normalization of amygdala and insula activity during scene processing. In addition, oxytocin normalized the abnormal coupling between amygdala activity and gaze behavior across all scenes in BPD participants. Overall, these findings suggest that oxytocin may be capable of attenuating BPD patients’ hypersensitivity for complex scenes, irrespective of their valence.
Advance access publication date: 9 October 2017
Gesehen am 15.10.2018